OPTIMIZATION OF PLANS OF EXPERIMENTS IN CONDITIONS OF LIMITED MATERIAL AND TIME RESOURCES - Костенко, О. М. (Scientific Progress & Innovations, 2015)
The article is devoted of solving scientific and technical problems of reduce material and time costs in implementing experimental research through the development and implementation of methods for the synthesis of optimal plans experiments in conditions of limited material and time resources. The developed methodology includes optimization techniques for cost and time-consuming experiment plans: based on the use of standard serial sequences of plans of multifactorial experiment, composite construction method of plans which are close to optimal, building a catalog of tipical plans, iterative experiments planning, serial planning experiments, identification of dynamic objects on the basis of iterative planning. The methodology has been tested in the study of some technological processes, devices and systems.